Modulation of the One Health Approach to Tackle Brucellosis in Buffaloes and Cattle in Two Italian Territories with Different Characteristics - Mazzeo, Alessandra; Tremonte, Patrizio; Rossi, Nicola; Ferrara, Carlo; Mascolo, Celestina; Lombardi, Silvia Jane; Sorrentino, Elena (Journal of Buffalo Science, 2023)
The new European Union animal health law and its rule concerning brucellosis in cattle and buffaloes The authors examine the latest European Union (EU) rules concerning eradication and surveillance of brucellosis and animal infectious diseases of EU concern. The Italian rules concerning brucellosis in cattle and buffaloes Italy is included in the EU co-financed compulsory eradication and surveillance programmes for brucellosis in cattle and in buffaloes in the frame of the EU and the related Italian laws, which allowed reaching the Brucellosis Free status without vaccination (former "Officially Brucellosis Free - OBF" status) in the majority of the northern and middle Italian Regions and in some middle and southern Provinces included in Regions where the infection persists. Epidemiology of brucellosis in the EU and in Italy In the Italian Province of Caserta, the highest prevalence of brucellosis in buffaloes is reported; in 2017-2021, a total of 314 outbreaks occurred, in which 39,163 heads tested positive. Here, brucellosis is threatening not only human health and the widespread buffaloes breeding but also the important satellite activities concerning the Protected Designation of Origin (P.O.D.) cheese “Mozzarella di Bufala Campana". The authors also discuss the reemerged brucellosis in cattle in the Molise Region, which despite bordering the Province of Caserta, shows different hydrographic, orographic, and breeding characteristics. In Molise, the reemerged brucellosis had a very different epidemiological course, which allowed it to limit the adoption of One Health measures. The One Health approach to tackle brucellosis in buffaloes In order to tackle brucellosis in Campania Region and in its Province of Caserta, the One Health approach has been predisposed through strict control of animal health, human health, and the environment. The adopted model could be exportable to territories having similar characteristics.